The path of least resistance: The unusual extradigestive journey of a nasogastric tube following oropharyngeal perforation - Anass Benomar, MD, MSc, FRCPC; Rui-Ning Gong, MD; An Ni Wu, MD; Michele Khayat, MD; Hamza Laref, DMD, MD; Marc-Jacques Dubois, MD, FRCPC; Pierre Bourgouin, MD, FRCPC; Patrick P. Bourgouin, MD, FRCPC (Radiology Case Reports)
Nasogastric tube placement is frequently performed in various medical settings. While generally deemed safe in patients without risk factors, complications may occur due to malposition, justifying the need of systematic confirmation of position with chest radiographs. We present the case of a critically ill male adult patient for whom the tube position was initially deemed very unusual on postinsertion radiographs, prompting further workup which ultimately confirmed an oropharyngeal perforation with a left parapharyngeal, left visceral, retrotracheal, and right retrodiaphragmatic course, and resulting in a recurrent pneumothorax and empyema treated by surgical decortication.